KEBIJAKAN LEGALITAS INDUSTRI PENGOLAHAN BAHAN BAKU KAYU LIMBAH INDUSTRI PRIMER KAYU BULAT (STUDI KASUS KECAMATAN BANJARMASIN UTARA KOTA BANJARMASIN) - Krismandra Natalis Wiratmaja; Daniel Itta; Zainal Abidin (Lambung Mangkurat University-Indonesia, 2021)
The increased development of residential areas and community facilities in the South Kalimantan region, especially in Banjarmasin and its surroundings, increased demand for wood, The research objectives were to identify the problems of small industry entrepreneurs with waste wood/sibitan raw material. The research period was 5 (five) months, from the end of January 2020 to the end of April 2020, which included the preparation of research proposals, research, data processing, and reporting. The results of the research were: a) the high level of community demand for sawn wood as a basic material for building houses and the dependence of the Banjarmasin Utara Subdistrict community on the presence of the wood industry was important factors for the existence of the wood industry with raw material from industrial waste wood; b) Laws and Ministerial Regulations stipulated that the licensing authority for a logging industry is carried out by the forestry service, while for every other industry it is regulated by the Industry and Trade office; c) the solution to fulfilling the requirements for obtaining a small industry license is a guarantee that the supply of raw materials can be obtained from three alternatives, namely; source of raw materials from the waste of business permit for the Primary Industries of Timber Forest Products (IUIPHHK), People’s Plantations (HTR), and rejected wood, and d) draft policy on the legality of the wood industry with raw material from waste wood. An industrial company can obtain a permit by meeting the requirements,